Learning Multi-level Features For Sensor-based Human Action Recognition - Xu, Yan; Shen, Zhengyang; Zhang, Xin; Gao, Yifan; Deng, Shujian; Wang, Yipei; Fan, Yubo; Chang, Eric (Pervasive and Mobile Computing, 2017)
This paper proposes a multi-level feature learning framework for human action recognition using a single body-worn inertial sensor. The framework consists of three phases, respectively designed to analyze signal-based (low-level), components (mid-level) and semantic (high-level) information. Low-level features capture the time and frequency domain property while mid-level representations learn the composition of the action. The Maxmargin Latent Pattern Learning (MLPL) method is proposed to learn high-level semantic descriptions of latent action patterns as the output of our framework. The proposed method achieves the state-of-the-art performances, 88.7%, 98.8% and 72.6% (weighted F1 score) respectively, on Skoda, WISDM and OPP datasets.